Environmental study of azole‐resistant Aspergillus fumigatus with TR34/L98H mutations in the cyp51A gene in Iran. Issue 6 (14th May 2013) - Badali, Hamid; Vaezi, Afsane; Haghani, Iman; Yazdanparast, Seyed A.; Hedayati, Mohammad T.; Mousavi, Bita; Ansari, Saham; Hagen, Ferry; Meis, Jacques F.; Chowdhary, Anuradha
Summary: Azole resistance in Aspergillus is emerging in European and Asian countries. As azoles are mainstay of therapy in the management of aspergillosis, azole resistance has serious implications in patient management. We report the emergence of resistance to triazoles in environmental Aspergillus fumigatus isolates in Iran. The TR34 /L98H mutation was the only resistance mechanism. Overall 3.3% of the A. fumigatus isolates from hospital surroundings in Sari and Tehran had the same TR34 /L98H STR Af genotype and were related to some resistant clinical and environmental TR34 /L98H isolates from the Netherlands and India. It is emphasised that routine resistance surveillance studies focusing on environmental and clinical samples are warranted to yield the true prevalence of azole resistance in A. fumigatus in Iran.